The Effect Of Knowledge Sharing Behavior, Organizational Culture And Work Discipline On The Work Achievement Of Employees Of PT. Yogyakarta People's Daily - Fariel Muhammad (Universitas Muhammadiyah Makassar, 2022)
The purpose of this study is to determine whether employees are satisfied with the system implemented by the company in terms of discipline and culture in the company and whether this has an effect. PT. Harian Kedaulatan Rakyat. This survey research method uses data collection and analysis techniques in the form of opinions/facts from the subjects studied (respondents) through question and answer using questionnaires (oralquestions) which are directly communicated with respondents, and intervies (oralquestions). The study will explain the relationship between influencing and being influenced by the variables studied,namely the behavior of various knowledge,organizational culture, work discipline, and employee performance. 100 respondents employees of PT. Harian Kedaulatan Rakyat has a positive and significant of the data that has been obtained